Integrative career readiness model using psychological construct. - Mohd. Kosnin, Azlina (Areadiscover, 2022)
Career readiness is an important element needed by students to enable them to manage their transition from university to the career world. This study explores the psychological elements of personality and career efficacy in helping to predict the career readiness of undergraduate students at university. The study was conducted on 311 students in the final year of their first degree. By using SMARTPLS software through the Partial Least Square Structural Equation Modelling (PLS-SEM) measurement method, the significant relationship that exists between the variables studied proves the importance of personality traits and career efficacy in producing career readiness. The significant relationship between the variables then results in a model of career readiness that has coefficient of determination and predictive relevance at a moderate level. The elements studied in this study are psychological constructs that have been proven to have an impact on more positive behavioural changes. The relationship that exists between these elements can not only help produce graduates who have self-confidence but can also contribute to the production of graduates who have career readiness to function as human capital better in the career market.